The nature and control of organic compounds in soda ash evaporate production - Masemola, Patricia Mmoniemang (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2000)
Solar evaporite systems are man-managed ecosystems which are highly vulnerable to biological,physical and chemical disturbances. The problems encountered in such systems are in many cases found to be associated with the microbial ecology and the design of the system. This project focussed on investigating the nature of organic compounds contaminating soda ash produced at a solar evaporite production system located at Sua Pan in Botswana. Several years after the plant was commissioned, problems, including accumulation of total organic carbon (TOC) and discolouration of the soda ash product were encountered. The salt produced also retained high moisture content and was coloured pink. These phenomena impacted severely on the economic performance of the enterprise. This study was aimed at determining the origin and fate of these organic compounds within the system in order to elucidate the nature of the problem and also to conceptualise a remediation strategy suitable to reducing its impact. This was achieved by analysis of both dialysed and solvent extracts of the influent brine (well-brine), brine in the ponds (T-brine) and the bicarbonate filter cake. Although complete identification of the organic compounds isolated was not undertaken in this study, spectroscopic analysis of compounds isolated, by UV, IR, NMR and MS, strongly indicated that fulvic acids, a component of the influent well-brine organics, contribute to the organic contamination of the final product. Part of this component, however, is degraded during the ponding process. It was shown that an extracellular polysaccharide (EPS) produced by Dunaliella. spp., which proliferates in the evaporation ponds, contributes in a major way to the accumulation of TOC in the system. This was demonstrated by relating the sugar profile of carbohydrates isolated from the pond brine and final product, being arabinose, xylose, 2-o-methyl hexose, mannose, glucose and galactose. Studies reported show that EPS production was enhanced when algal cultures were exposed to stress conditions of high illumination, increasing salinity and temperature, and nitrogen limitation. Studies undertaken for the development of a remediation process for this system have shown that nutrient stripping and bacterial systems could be applied to deal with the dissolved TOC fraction, whereas adsorption systems could deal with the particulate fractions. Algal systems showed most potential for the removal of nutrients in the influent well-brine compared to chemical processes.Complete removal of ammonium and phosphorus removal efficiencies of pproximately 50% were achieved in an unoptimised pilot-scale Dunaliella-based HRAP. While similar effects were demonstrated for chemical processes, some economic constraints were noted. The potential of halophilic bacterial systems for the degradation of organic compounds in brine was also demonstrated. The limitations on the performance of such systems, associated with the low metabolic diversity, and poor immobilisation of physico-chemical processes were found to have a very low impact on the dissolved TOC fraction of the brine, the removal of the particulate material was found to result in a 35% TOC reduction in the final soda ash product and the production of a white final product.halobacteria, however, were noted. Although physico-chemical processes were found to have a very low impact on the dissolved TOC fraction of the brine, the removal of the particulate material was found to result in a 35% TOC reduction in the final soda ash product and the production of a white final product. Apart from a description of the microbial ecology of the ponds and the identification of major contributions to the TOC of the final product, a number of remediation strategies were evaluated and are described. These include chemical and biological stripping of nutrients sustaining microbial TOC production in the ponds, and also biological and physico-chemical processes for their removal once formed. Future studies to undertake the further development of these proposals has been described
Keywords: Organic compounds; Biotic communities; Sua Pan Soda Ash Project -- Botswana